Arterial Stiffness and Cardiovascular Therapy. (7th August 2014) - Janić, Miodrag; Lunder, Mojca; Šabovič, Mišo
Abstract : The world population is aging and the number of old people is continuously increasing. Arterial structure and function change with age, progressively leading to arterial stiffening. Arterial stiffness is best characterized by measurement of pulse wave velocity (PWV), which is its surrogate marker. It has been shown that PWV could improve cardiovascular event prediction in models that included standard risk factors. Consequently, it might therefore enable better identification of populations at high-risk of cardiovascular morbidity and mortality. The present review is focused on a survey of different pharmacological therapeutic options for decreasing arterial stiffness. The influence of several groups of drugs is described: antihypertensive drugs (angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, calcium channel blockers, beta-blockers, diuretics, and nitrates), statins, peroral antidiabetics, advanced glycation end-products (AGE) cross-link breakers, anti-inflammatory drugs, endothelin-A receptor antagonists, and vasopeptidase inhibitors. All of these have shown some effect in decreasing arterial stiffness. Nevertheless, further studies are needed which should address the influence of arterial stiffness diminishment on major adverse cardiovascular and cerebrovascular events (MACCE).